STEP-NC Interpolator for General 2D and 3D Parametric Curve / Dzullijah Ibrahim...[et al.] - Ibrahim, Dzullijah; Yaakob, Yusli; Hussin, Norasikin; Samad, Zahurin (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The development of Open Architecture (PC-based) Numerical Control (OAPC-NC) Interpolator has enhanced the possibilities of data communication between the systems. In specialty domain, such as design, manufacturing, and machining, the STEP AP238 (STEP-NC) is developed. A STEP-NC interface to OAPC-NC interpolator using STEP-NC tool path data is proposed and developed. A hierarchical-based algorithm is used to extract the tool path data from STEP-NC tool path file of a product model. The generated output of the interpolated data is computer simulated for 2D circular-arc paths and 3D linear paths to verify the validity of the interpolator input generated by the proposed interface.